The determination of tenofovir level in breast milk of nursing mothers under tenofovir therapy - Ertürk, Ümran Sümeyye; Mete, Bilgül; Özaras, Reşat; Saltoğlu, Neşe; Balkan, İlker İnanç; Mert, Ali; Kaçmaz, Bahar; Sağlam, Onursal; Güney, Berrak; Sayman, Özden Aksu; Tabak, Fehmi (Wiley, 2018)
In this study, we aimed to determine of tenofovir concentration in maternal plasma, breast milk and plasma of infants and factors affecting drug levels in chronic hepatitis B (CHB) patients using tenofovir disoproxil fumarate (TDF) during breastfeeding period.
Annual Meeting of the American-Association-for-the-Study-of-Liver-Diseases (AASLD) / Liver Meeting -- NOV 09-13, 2018 -- San Francisco, CA
WOS: 000446020500434